Urdu quad o insha pardazi - Mah Laqa rafeeq (Ferozesons; Lahore, 2008)
Urdu Quad-o-Insha Pardazi focuses on developing skills in Urdu composition and essay writing, emphasizing structure, style, and creativity in crafting meaningful texts.